The moderating effects of self efficacy on the relationship between personality traits and cigarette smoking behaviour among adolescent in Iran - Golestan, Samira; Hamsan, Hanina H.; Abdullah, Haslinda (Canadian Center of Science and Education, 2015)
This paper aims to examine the relationship between personality traits (extraversion, neuroticism, agreeableness, openness, and conscientiousness) and cigarette smoking behavior and also determine the moderating effect of self-efficacy on the relationship between personality traits and cigarette smoking behavior among adolescents in Kerman, Iran. A quantitative research method was employed. The samples included three hundred current smoker adolescents between the ages of 15 to 18. The data was collected by means of self-administered questionnaires and then analyzed by AMOS software. The direct structural model was employed to figure out the path relationships between personality traits (extraversion, neuroticism, agreeableness, openness, and conscientiousness) and cigarette smoking behavior. In addition, a multi-group analysis approach was applied to assess the moderating effect of self-efficacy on the relationship between personality traits (extraversion, neuroticism, agreeableness, openness, and conscientiousness) and cigarette smoking behavior among adolescents. The results of testing the structural equation model showed that there were significant relationships between personality traits (neuroticism and conscientiousness) and cigarette smoking behavior whereas there was no significant relationship between personality traits (extraversion, agreeableness and openness) and cigarette smoking behavior. Also, the results related to the moderating effect of self-efficacy revealed that self-efficacy significantly moderated the effect of neuroticism on cigarette smoking behavior but did not moderate the relationship of other personality traits i.e. extraversion, openness, agreeableness and conscientiousness with and cigarette smoking behavior. At the end, this study recommends some solutions in order to prevent cigarette smoking behavior among adolescents.